1998
DOI: 10.1051/agro:19980802
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in the incidence of Trichoderma spp. using substrate supplementation with peat and an alternative spawn during cultivation of Lentinula edodes on pasteurised wheat straw

Abstract: -Shiitake, Lentinula

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The BE values for strains S610 (50.2 %), M115 (53.27 %), and IE-40 (55.6 %) coincide with data cited by Mata et al [22] (24±59%). They cultivated the same strains on wheat straw with peat moss pasteurized at 65 C for 24 h. Savoie et al [32] also described the utilization of pasteurized wheat straw, which was subjected to several treatments; employed for four of the strains evaluated in this study (A9, S610, M115, IE-40).…”
Section: Resultssupporting
confidence: 89%
“…The BE values for strains S610 (50.2 %), M115 (53.27 %), and IE-40 (55.6 %) coincide with data cited by Mata et al [22] (24±59%). They cultivated the same strains on wheat straw with peat moss pasteurized at 65 C for 24 h. Savoie et al [32] also described the utilization of pasteurized wheat straw, which was subjected to several treatments; employed for four of the strains evaluated in this study (A9, S610, M115, IE-40).…”
Section: Resultssupporting
confidence: 89%
“…Mata et al (1998) used wheat straw pasteurized at 65 °C and supplemented. In that study, BE was 38% and 44%.…”
Section: Resultsmentioning
confidence: 99%
“…The number of shiitake strains that are well adapted to grow on pasteurized wheat straw is relatively low (Levanon et al , 1993; Mata and Savoie, 1998; Mata et al , 2002) and this substrate is easily contaminated with antagonistic fungi. However, it has been demonstrated that the use of supplemented spawn reduces substrate contamination considerably (Mata et al , 1998; Sovoie et al , 2000). …”
Section: Introductionmentioning
confidence: 99%
“…He also found that endoglucanase and β-glucosidase activity increased slightly at the time of fruiting. Mata et al (30) have mentioned that endoglucanase production is associated with other primordium and fruiting formation stages where there has been a significant increase in enzymatic activity. As we found in this study, Leatham and Leonard (22) mentioned that, during mycelial growth, L. edodes uses the most accessible sources of carbon, such as free sugars, starch, pectins and hemicelluloses.…”
Section: Resultsmentioning
confidence: 99%